ENTRY BARRIER Antara Persaingan Potensial dan Aktual - Widiyanto, Ibnu (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2006)
One of the five forces in industrial competition is entry barrier because the existence of entry barrier Is likely to impede (potential or actual) competition effectiveness. This paper is designed to analyze the Indonesia's competition of industry. Using an educated judgment method, the study attempts to characterize the main cause and the degree of entry barrier in Indonesia's industries.Â The results show that the trade sector has the highest degree of entry barrier which is not set by a government protection. Further, in general, there is a positive correlation between the degree of entry barrier and its contribution to total industrial output. However, entry barrier as a result of a successÂ from the marketing program of a firm may be a paradox in competition.